2019
DOI: 10.1111/jan.13933
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of coping styles and self‐efficacy between perceived stress and satisfaction with QOL in Chinese adolescents with type 1 diabetes

Abstract: Aims (a) To explore the effect of perceived stress on satisfaction with quality of life (QOL) among Chinese adolescents with type 1 diabetes (T1D); and (b) to determine if coping styles and self‐efficacy are mediators of the association between perceived stress and satisfaction with QOL. Background Adolescents with T1D experience ongoing stress related to a complex treatment regimen and live with a condition that differentiates them from their peers. It is important to know how adolescents with T1D cope with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
4
13
0
2
Order By: Relevance
“…In line with previous studies (Lin et al, ; Rohan et al, ), we found that self‐management was significantly and positively related to better control of HbA 1c . Corresponding to the low level of self‐management, nearly half of the participants in this study did not achieve the HbA 1c control target; This result was similar to Yang's finding (Yang et al, ). Therefore, greater attention should be paid to both family‐ and individual‐related factors that influence self‐management and glycaemic control among Chinese youth with T1D.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with previous studies (Lin et al, ; Rohan et al, ), we found that self‐management was significantly and positively related to better control of HbA 1c . Corresponding to the low level of self‐management, nearly half of the participants in this study did not achieve the HbA 1c control target; This result was similar to Yang's finding (Yang et al, ). Therefore, greater attention should be paid to both family‐ and individual‐related factors that influence self‐management and glycaemic control among Chinese youth with T1D.…”
Section: Discussionsupporting
confidence: 87%
“…However, studies showed that youths are at increased risk for suboptimal glycaemic control (Hartl, Seiffge-Krenke, & Laursen, 2015;Schwandt et al, 2017). According to studies from mainland China, youth had an average HbA 1c ranging from 8.25%-9.2% and more than 50% of these youth failed to achieve the goal of glycaemic control, namely, HbA 1c below 7.5% (Huo et al, 2018;McGuire et al, 2017;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When nurses experience a high rate of workplace stress, they will have increased feeling of illness, such as headaches, gastrointestinal upset, insomnia, upper respiratory tract infections, dizziness or depression (Callaghan et al, ). Additionally, several empirical studies have shown that WS significantly influenced nurses' burnout (Khamisa et al, ), perceived social support (PSS) (Jin, Zhang, Li, Deng, & Gao, ), self‐efficacy (Yang et al, ) and job satisfaction (Khamisa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown a bivariate effect between WS, self‐efficacy, PSS and burnout (Babaeiamiri, ; Hu et al, ; Jin et al, ; Khamisa et al, ; Laschinger et al, ; Yang et al, ), no studies have been found to put these variables in one model simultaneously. Therefore, according to Lazarus and Folkman's () Cognitive Theory of Stress and empirical evidence, we proposed this model to explore in‐depth the structural relationships between the study variables and determine the degree of their influences.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐efficacy and coping with stress in chronic diseases affect the course of the disease (Ceyhan & Unsal, 2018; Knowles et al, 2020; Ozdemir & Tasci, 2013; Tielemans et al, 2015). International studies on these issues related to chronic diseases observed that there was a relationship between patients’ self‐efficacies and their coping strategies in many disease groups such as stroke, cancer, diabetes mellitus, respiratory system diseases and joint/connective tissue diseases (Benka et al, 2014; Calık Var et al, 2016; Ceyhan & Unsal, 2018; Chirico, Lucidi, et al, 2017; Geng et al, 2018; Knowles et al, 2020; Koehler et al, 2009; Saconi et al, 2020; Tielemans et al, 2015; Yang et al, 2019; Zhang et al, 2008). There was a strong relationship between coping and self‐efficacy of patients with cancer and stroke (Chirico, Lucidi, et al, 2017; Chirico, Serpentini, et al, 2017; Geng et al, 2018; Koehler et al, 2009; Tielemans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%